Comparative evaluation of attitude of teaching faculties and interns of a health sciences university toward geriatric people using Kogan's attitudes toward old people scale: A cross-sectional study - Harekrishna J Raval; Neerja Mahajan; Rajesh Sethuraman (Wolters Kluwer Medknow Publications, 2018)
Context: Positive reforms in the existing curriculum of health universities to sensitize the health-care providers in having appreciative attitudes toward elderly are always desirable. However, baseline data as need assessment exercises for the same are deficient in the literature. Aims: This study used a cross-sectional approach to evaluate and compare the attitudes of teaching faculties and interns of a health sciences university using Kogan's attitude scale toward old people. Subjects and Methods: A total of 369 teaching faculties and interns participated according to inclusion criteria of the study. A questionnaire survey forms were given to each participant along with participant information sheet after consent from each participant was obtained. The Kogan's attitudes toward old people scale were used which comprised 34 items, containing 17 positive and 17 negative statements. Statistical Analysis Used: One-way ANOVA and Tukey's post hoc test were used in the statistical analysis. Results: The mean Kogan's score of all four participated institutes showed neutral attitude of staff and students toward old people. Conclusions: The general attitude by mean Kogan's score was seen as neutral in all the four participating colleges. Hence, some positive reforms in the existing curriculum are desirable to reinforce the attitudes of health-care providers toward older people.